Study of disturbance wave development in downwards annular flows with a moving frameofreference brightnessbased laserinduced fluorescence method - An,JS; Cherdantsev,A; Zadrazil,I; Markides,C (Experiments in Fluids, 2020)
A novel moving frame-of-reference brightness-based laser-induced fluorescence (MFoR-BBLIF) method was developed and demonstrated in downwards co-current air–water annular flows. The method was applied to study the downstream develop- ment of individual disturbance waves in flows over a range of conditions (ReL = 276–1321, ReG = 39,500–79,000). In this method, the optical measurement system, and hence, the region of interrogation (ROI) was translated physically along the length of the test-section with a velocity close to that of individual disturbance waves to obtain the velocities of individual disturbance-waves as a function of downstream distance from the inlet. It was found that the velocities of individual distur- bance waves increase with both downstream distance and gas–liquid flow conditions. In addition, the variation in the wave velocities was more significant at higher gas and liquid Reynolds numbers. The approach can be integrated with many other contactless measurement methods, and can also be used over a range of translation speeds (not necessarily in a “Lagrangian” manner) to study the evolution of important advecting flow phenomena.